A study on decision criteria for assessing construction readiness of highway projects - Nur Afiqah, Mohd Radzi (2021)
The impact of highway construction delays is not limited to the construction industry but also affects the nation’s overall economic and social conditions. In addition, delays in highway projects across the country have seriously eroded the confidence of foreign investors and the local business community. One of the factors that cause delay to highway projects is that project teams tend to rush into construction without assessing the readiness of the project. Adequately assessing the readiness of a project may prevent delay. Therefore, this study aims to identify the key decision criteria (KDC) specifically for assessing the construction readiness of highway projects. To achieve that aim, the objectives are to: (1) identify decision criteria specifically for assessing the construction readiness of highway projects; (2) determine the key decision criteria for construction readiness assessment; and (3) evaluate the relationship between the key decision criteria. The scope of this research is the construction industry with the primary focus being the highway construction projects in Malaysia. In phase I of the study, interviews with fifteen industry practitioners working on highway construction projects are being conducted and analysed. Then, in phase II, data from 109 responses are analysed using the mean ranking technique, normalization, Least Significant Difference (LSD) test, and agreement analysis. In phase III, using factor analysis, the relationships between the key decision criteria are examined. A total of eighteen KDCs to assess the readiness of highway projects are identified. The key decision criteria are grouped into four categories reduced uncertainties, availability of resources, approvals and permits, and adequate traffic management plan. In conclusion, construction readiness not only can be assessed during the execution phase, but it can be assessed during the start - up phase. These identified key decision criteria can help industry practitioners to assess their projects before mobilizing their highway construction project. Hence, avoiding impacts from premature starts such as schedule slippage, poor worker productivity, and production delay. In addition, these KDC can help policymakers to take suitable measures to prevent premature starts and mitigate delays, thus avoiding negative impacts to economic and social growth. Also, researchers can use the identified KDCs and their relationship to develop decision support tool for assessing construction readiness in highway construction projects.